Deteksi Gen P14ARF Pada Spesimen Blok Parafin Lidah Penderita Karsinoma Sel Skuamosa Di RSUD Dr. Moewardi - Jinan Fairuz Anindika Rakhmat; Pradipto Subiyantoro; Vita Nirmala A (Nexus Biomedika, 2013)
Background : The oral cavity cancer is twenty most common cancer that occurs in the world.Around90%oral cavity cancer cell carcinoma is squamous andmost of the incidents come from tongue. p14ARF gene is one of the tumor suppressor gene that can prevent the occurrence of a tumor. The purpose of this research was to know the existence of p14ARF gene in paraffin block specimens of the tongue of the squamous cell carcinoma patients in the Regional Public Hospital Dr. Moewardi. Methods : This studywas explorative and descriptive research. Paraffin block samples of the tongue squamous cell carcinoma patients were used in this study. The objectof this research was p14ARF gene located on chromosomes 9p21. The samples were separated from the Paraffin Block and their DNAwere isolated. The DNA products, then, were amplified byPCR and their PCR products were runin agarose gel electrophoresis. Later, the gel was visualized withGel Documentation and analyzed to detect the p14ARF gene. Results : On the visualisation of the gel product, the p14ARF gene was detected in one sample with atypical band pattern and it was not detected on the eight other samples. Conclusion : Only one sample of the tongue squamous cell carcinoma patients which was positive expressed p14ARF gene with atypical band pattern while the eight other samples were not. Keywords : tongue squamous cell carcinoma, p14ARF, oral cavity cancer